A QUALITATIVE STUDY INTO MOTIVATIONAL STRATEGIES UTILIZED BY INDONESIAN EFL UNDERGRADUATE STUDENTS - Ayu Tri Safika (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
In recent years, numerous studies worldwide have investigated students' motivation to learn English, but few have explored the strategies used to inspire them to continue learning English. This research aims to examine the approaches employed by undergraduate students to maintain their motivation in learning English, which can provide valuable insights for readers facing low motivation. This study follows a narrative inquiry design, involving two sixth-semester participants who study English Foreign Language at a university in Jember. The researcher conducted semi-structured interviews and subsequently analyzed the data thematically. Upon analysis of the interviews, it became apparent that the challenges participants encountered in learning English encompassed issues like expanding vocabulary, understanding grammar, improving pronunciation, enhancing oral communication, as well as reading and writing skills. They apply metacognitive and cognitive strategies to overcome their challenges. Furthermore, their lecturers provide them with frequent feedback to correct their mistakes, in line with the social approach. In addition their motivation to persist in learning English was driven by internal and external factors. Students have different motivations for learning English, including academic goals and personal interest. They revisit their reasons for learning when motivation declines. Learning approaches differ, with some students favoring structured study times and others engaging in activities like reading and listening. Both motivation and learning methods have a significant impact on their English language learning achievements, leading to positive progress in their journey.